2020
DOI: 10.3390/molecules25071506
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences of the Effect of Lipoproteins and Apolipoproteins on 10-Year Cardiovascular Disease Risk; Insights from the ATTICA Study (2002–2012)

Abstract: The sex-specific effect of lipid-related biomarkers on 10-year first fatal/non fatal cardiovascular disease (CVD) incidence was evaluated. ATTICA study was conducted during 2001–2012. n = 1514 men and n = 1528 women (>18 years) from greater Athens area, Greece were recruited. Follow-up (2011–2012) was achieved in n = 2020 participants. Baseline lipid profile was measured. Overall CVD event was 15.5% (n = 317) (19.7% in men and 11.7% in women, p < 0.001). High density lipoprotein cholesterol (HDL-C) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…A multicenter study ( 22 ) found that postmenopausal women with higher non-HDL-C/HDL-C ratios had a greater chance of developing carotid atherosclerotic plaque ( OR : 1.30, 95% CI : 1.07–1.58, p = 0.009) when adjusted for other cardiovascular risk factors. Recently, studies found that the non-HDL-C/HDL-C ratio might be a more accurate predictor of cardiovascular disease ( 26 , 27 ). In addition, an asymptomatic polyvascular abnormalities in Community study ( 37 ) found that the odds of unstable carotid plaques at non-HDL-C levels in the middle and highest trilaterals were 1.02 (95% CI , 0.84–1.23) and 1.50 (95% CI , 1.23–1.82), respectively, after adjusting for confounders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multicenter study ( 22 ) found that postmenopausal women with higher non-HDL-C/HDL-C ratios had a greater chance of developing carotid atherosclerotic plaque ( OR : 1.30, 95% CI : 1.07–1.58, p = 0.009) when adjusted for other cardiovascular risk factors. Recently, studies found that the non-HDL-C/HDL-C ratio might be a more accurate predictor of cardiovascular disease ( 26 , 27 ). In addition, an asymptomatic polyvascular abnormalities in Community study ( 37 ) found that the odds of unstable carotid plaques at non-HDL-C levels in the middle and highest trilaterals were 1.02 (95% CI , 0.84–1.23) and 1.50 (95% CI , 1.23–1.82), respectively, after adjusting for confounders.…”
Section: Discussionmentioning
confidence: 99%
“…The thicker the lipid core, the more likely it is to cause expansion of the necrotic core of the plaque, resulting in plaque rupture ( 25 ). Moreover, recently studies showed that the non-HDL-C/HDL-C ratio might be a better predictor of cardiovascular events than traditional lipid indices ( 26 , 27 ). However, to date, there is no data on evaluating the association between non-HDL-C/HDL-C ratio and carotid plaque stability.…”
Section: Introductionmentioning
confidence: 99%
“…The non-HDL-C/HDL-C ratio, which represents the ratio of atherogenic factors to anti-atherogenic factors, has been shown to correlate with various dyslipidemia-related diseases, including diabetes mellitus and metabolic syndrome. 41 , 42 Studies have shown that it may be a more accurate predictor of cardiovascular disease than the traditional lipid index, 43 and high non-HDL-C/HDL-C ratios are strongly associated with poorer overall survival in peritoneal dialysis patients. 44 In addition, an independent association has been found with carotid plaque lipid cores.…”
Section: Discussionmentioning
confidence: 99%
“…First, some unmeasured confounders such as dietary fatty acids and carbohydrates ( 23 ), oils and solid fats ( 24 ) and some diseases include hepatitis ( 25 ) and nephrotic syndrome may have effects on the association of non-HDL-C and ASCVD. Second, Our study has unbalanced distributions of gender while the sex-specific effect of lipid-related biomarkers has been evaluated ( 26 ). Third, the sample was predominantly Chinese, and thus this finding may not be consistent in other racial groups.…”
Section: Discussionmentioning
confidence: 99%